2013
DOI: 10.1136/bmjopen-2012-002525
|View full text |Cite
|
Sign up to set email alerts
|

What determines patient satisfaction with surgery? A prospective cohort study of 4709 patients following total joint replacement

Abstract: ObjectivesTo investigate the factors which influence patient satisfaction with surgical services and to explore the relationship between overall satisfaction, satisfaction with specific facets of outcome and measured clinical outcomes (patient reported outcome measures (PROMs)).DesignProspective cohort study.SettingSingle National Health Service (NHS) teaching hospital.Participants4709 individuals undergoing primary lower limb joint replacement over a 4-year period (January 2006–December 2010).Main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
267
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(297 citation statements)
references
References 32 publications
12
267
2
5
Order By: Relevance
“…In the present study, the patients had low postoperative pain scores irrespective of which study group they belonged to, both at rest and during mobilization. This indicates that the multimodal pain regimen that we used was safe, simple, and satisfactory—and that the patient’s preoperative expectations were met through information and education (Hamilton et al 2013). …”
Section: Discussionmentioning
confidence: 91%
“…In the present study, the patients had low postoperative pain scores irrespective of which study group they belonged to, both at rest and during mobilization. This indicates that the multimodal pain regimen that we used was safe, simple, and satisfactory—and that the patient’s preoperative expectations were met through information and education (Hamilton et al 2013). …”
Section: Discussionmentioning
confidence: 91%
“…31,32 While receipt of discretionary care may contribute to higher patient satisfaction with health care providers, we do not believe it is the sole determinant of patient satisfaction. Many features of the health care experience likely contribute to satisfaction with health care providers, including whether care met patients' expectations, 11,[33][34][35] shorter rather than longer waiting times, 36 -38 and the quality of communication with physician and nonphysician staff. 36,38,39 In particular, patient-centered communication may enhance the doctor-patient relationship while encouraging efficient, effective care.…”
Section: Discussionmentioning
confidence: 99%
“…Also patient satisfaction is perhaps one of the most important criterion of success, especially in service industries. 7 The potential advantage of SUTI is its reduction in the number of skin incisions, which in turn might translate into less postoperative pain, a shorter convalescence, 3 and also a good wound cosmesis. 4 The safety and feasibility outcome results from a current study, which is designed to compare SUTI-TEP and C-TEP procedures, have shown no differences in length of hospital stay, POD 7 th pain VAS score, postoperative complications, and chronic pain just like as demonstrated by other papers.…”
Section: Discussionmentioning
confidence: 99%
“…After putting all three factors together; (1) meeting preoperative expectations (cosmetic outcome) (2) satisfaction with pain relief (3) satisfaction with hospital environment. 7 Patient demographics and perioperative outcomes of SUTI-TEP were analyzed and compared with those of C-TEP.…”
Section: Methodsmentioning
confidence: 99%